PENERAPAN METODE TANYA JAWAB DALAM MENGEMBANGKAN BAHASA EKSPRESIF ANAK USIA DINI - Fikri, Nabila; Depalina, Syamsiah (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
This study aims to describe the application of the question and answer method in developing expressive language skills in early childhood. Expressive language skills are one of the important indicators in the development of children's communication which includes the ability to express thoughts, feelings, and desires through words. This study uses a literature study approach by reviewing various relevant scientific books and journals. The results of the study show that the question and answer method carried out in a structured and interactive manner can improve children's ability to express opinions, answer questions, and convey ideas verbally. This study concludes that the question and answer method can be an effective strategy in supporting the development of expressive language in early childhood if it is carried out consistently and in accordance with the child's developmental level.